Therapeutic effects of different Atorvastatin doses on vulnerable plaques in coronary arteries assessed by intracoronary optical coherence tomography. Issue 31 (August 2018) - Ye, Honghua; Wang, Shiqi; Hu, Yewen; He, Fuwei; Ju, Jieqin; Cui, Hanbin; Chen, Xiaomin
Abstract : Abstract: The aim of this study was to evaluate optical coherence tomography (OCT) as an assessment of the efficacy of atorvastatin treatment. Twenty-four acute coronary syndrome (ACS) patients were allocated to conventional-dose (20 mg atorvastatin, n = 12) and intensive-dose (40–80 mg atorvastatin, n = 12) groups and correlations between changes in the OCT measurements and blood routine indexes were analyzed 9 months post-percutaneous coronary intervention (PCI). Treatment with atorvastatin resulted in a significant increase in the target thin cap fibroatheroma (TCFA) fibrous cap thicknesses in both groups. The increase was bigger in the intensive-dose group than in the conventional-dose group (184.1 ± 57.4 μm vs. 125.1 ± 28.6, P  = .005). The TCFA lipid core arc in both groups was significantly decreased compared with baseline (72.9 ± 29.3 vs. 127.6 ± 50.8, P  < .01 and 74.6 ± 32.9 vs. 132.6 ± 51.3, P  < .01, respectively). Correlation analyses showed an inverse relationship between low-density lipoprotein cholesterol (LDL-c) levels and the TCFA cap thickness, and a direct relationship between C-reactive protein (CRP) level and lipid core arc. Statins significantly increased the TCFA fibrous cap thickness and reduced the lipid core arc, and OCT measurements accurately reflected the levels of blood LDL-c and CRP. Trial registration: (Chinese Clinical Trial Registry) ChiCTR-IPR-17010874